2016
DOI: 10.1200/jco.2016.67.8250
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplantation Anti-CCR4 Antibody Mogamulizumab Against Adult T-Cell Leukemia/Lymphoma Is Associated With Significantly Increased Risks of Severe and Corticosteroid-Refractory Graft-Versus-Host Disease, Nonrelapse Mortality, and Overall Mortality

Abstract: Pretransplantation Mog was significantly associated with an increased risk of GVHD-related mortality, which supports the relevance of CCR4-expressing Tregs after allo-HSCT in humans. In clinical practice, Mog should be cautiously used for patients with ATLL who are eligible for allo-HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 33 publications
3
114
0
Order By: Relevance
“…Pretransplant Mog significantly improved the disease status before haplo-PBSCT. Moreover, a recent nationwide study of ATLL patients with pretransplant Mog in Japan showed that pretransplant Mog with intervals of <50 days to allo-HSCT was associated with increased risk of GVHD-related mortality [6]. In our case, the interval between pretransplant Mog and haplo-PBSCT was 49 days.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Pretransplant Mog significantly improved the disease status before haplo-PBSCT. Moreover, a recent nationwide study of ATLL patients with pretransplant Mog in Japan showed that pretransplant Mog with intervals of <50 days to allo-HSCT was associated with increased risk of GVHD-related mortality [6]. In our case, the interval between pretransplant Mog and haplo-PBSCT was 49 days.…”
mentioning
confidence: 67%
“…In our case, the interval between pretransplant Mog and haplo-PBSCT was 49 days. The nationwide study also pointed out the possibility that in vivo effector T cell depletion with anti-thymocyte globulin contributes to the reduction of severe aGVHD in ATLL patients with pretransplant Mog [6]. To our knowledge, our case is the first report of successful prevention of aGVHD with low-dose thymoglobulin in haplo-PBSCT following pretransplant Mog.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The use of mogamulizumab before allo-HSCT correlated with an increased risk of graft-versushost disease (GVHD)-related mortality. 24 Further studies are needed in order to clarify appropriate settings and patient populations that would benefit from treatments with mogamulizumab.…”
Section: Ccr4 Is Selectively Expressed On Th2 Cells Andmentioning
confidence: 99%
“…However, these studies were rather small to conduct multivariate analyses to adjust for the other risk factors of acute GVHD and other clinical events. Our group recently performed a retrospective analysis using a database of a nationwide survey of aggressive ATL (12). In this study, 82 patients out of 996 allo-HSCT recipients received moga before allo-HSCT.…”
Section: Foxp3mentioning
confidence: 99%